Sosialisasi Penggunaan Media Video Animasi Powton Guru SD Inpres 3/77 Panyili Kecamatan Palakka Kabupaten Bone - Abd. Hafid; Awaluddin Muin; Rosmalah; Satriani DH; Hardianti Hafid (Jurnal Abdi Masyarakat Pendidikan, 2025)
The purpose of this Community Service Program is to improve the pedagogical competence of teachers.. The target of the socialization on the use of Powtoon animated video media is the teachers of SD Inpres 3/77 Panyili, Palakka District, Bone Regency, as the participants. This socialization activity includes understanding the concept of Powtoon animated video media, the steps for creating Powtoon animated videos, and their use in learning. During the socialization, participants were provided with a guideline file for using Powtoon animated video media, enabling them to gain understanding and inspiration to apply it in their teaching practices. The results of the activity received positive responses from the participants because they gained knowledge about the use of animated video media and its practical application, which can help improve their pedagogical skills—particularly in designing and using Powtoon animated video media according to the learning objectives in elementary schools. This allows students to become more motivated, interested, active, and achieving. The conclusion of this activity is that participants gave positive responses regarding the practical knowledge and hands-on experience in using Powtoon animated video media, which can be utilized in learning to motivate students and enhance their interest and learning outcomes